2019
DOI: 10.1021/jacs.9b06528
|View full text |Cite
|
Sign up to set email alerts
|

Photoproximity Profiling of Protein–Protein Interactions in Cells

Abstract: Supplemental Figure 1: Chemical structures of photoproximity probes used in this study. Supplemental Figure 3: Sub-cellular localization and photocleavage with the PhotoPPI system. A) Fluorescence microscopy images of HeLa cells transiently transfected with SNAP-FLAG-NLS, which exhibit strong nuclear localization of the SNAP protein. B) Fluorescence and brightfield microscopy images of HeLa cells transientlytransfected with SNAP-FLAG-NLS show nuclear-localization of FITC signal in cells treated with the non-cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 28 publications
0
37
0
Order By: Relevance
“…Generation of reactive ectopic chemical entities is a generally useful strategy. For instance, several methods have deployed free, 60 or tethered 61 photoactivatable crosslinkers to study macromolecular interactomes. 62 But generation of ectopic molecules is not the only feat chemical biology is capable of.…”
Section: Precision Electrophile Delivery Methods To Roll-call Functional Subproteomesmentioning
confidence: 99%
“…Generation of reactive ectopic chemical entities is a generally useful strategy. For instance, several methods have deployed free, 60 or tethered 61 photoactivatable crosslinkers to study macromolecular interactomes. 62 But generation of ectopic molecules is not the only feat chemical biology is capable of.…”
Section: Precision Electrophile Delivery Methods To Roll-call Functional Subproteomesmentioning
confidence: 99%
“…Table 1 provides examples of reagents and conditions that are commonly used for the synthesis of dialkyldiazirines. 12,[62][63][64][65][66][67][68][69][70][71][72][73][74][75] Formation of the imine from 1 is typically carried out using ammonia, either in methanolic solution (entries 5-11) or condensed as a liquid (entries 1-4). For sterically hindered carbonyl substrates, imines can be accessed in two steps via formation of the cyclohexylamine imine/enamine or the O-nitroso oxime before treatment with ammonia (entries 10 and 11).…”
Section: Synthesismentioning
confidence: 99%
“…While some of these techniques have been successful, they also come with some significant limitations such as bias against weaker interactions, need for co-factors, and labelling approaches that require initiation by exogenous chemicals which have the potential to unsettle normal cellular homeostasis [95,96]. McCutcheon et al [97] reported a photo-proximity PPI (PhotoPPI) profiling method that allowed the characterization of PPI networking maps in vitro and in live cells. The authors employed a SNAP-tagged protein of interest (POI) and functionalized their DAZ-based probe with a benzylguanine and a photocleavable group (NO 2 -veratryl carbamate), such that the DAZ-functionalized probe was covalently attached to the POI (e.g., redox regulated sensor protein, KEAP1) by the benzylguanine moiety.…”
Section: Studying Complex Protein Interactionsmentioning
confidence: 99%
“…Subsequently, upon irradiation at 365 nm, the NO 2 -veratryl-carbamate group was cleaved off and any proximal proteins to the POI were simultaneously labelled by the DAZ group, thereby identifying any nearby proteins with the POI via a subsequent enrichment and quantitative LC-MS/MS analysis (Figure 16). This technique was used by the authors to elucidate the interactome for KEAP1, validate known interactions, and discover novel ones for KEAP1 with high temporal resolution in live cells [97]. This technique was used by the authors to elucidate the interactome for KEAP1, validate known interactions, and discover novel ones for KEAP1 with high temporal resolution in live cells [97].…”
Section: Studying Complex Protein Interactionsmentioning
confidence: 99%